(3LRA ef MOjK SYjO Hf YHO GdYRjR GdMdHis - (3YHO GdhgGH Hf GdMSf Hf GdhdjO GdcdCHjs
(3ChdgG (B:s
(3CNHQfG GdTjN GdGejf GHh GdWGgQ HQcGJ Hf GHQGgje GdbQTi QMeg Gdgd bQCg Ydjg hfMf fSY bGd MOKfG CHh eMeO YHO GdcQje Hf MeRI Hf GdMVQ GdSdei s
(3BNQgG (B:s
(3Ke bGd Gf YGbQ GdfGbI cGf ai QgW YRjRkG eKd GHf ReYg ai QgWg Ke bGd dYeO GMOce Edi GeQCJg ajVQHgG VQHkG Ke dYdg jaVi GdjgG ef jheg GhdjdJg BNQ GdMOjK hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HBNQg SeGYGJ cKjQIs
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdCMeOjI(B_ (3JhfS (B(5032(2)) s
Keywords: (3GdMOjK h GdeUWdMs